Features of decorative and applied solutions in the buildings of Akmolinsk - Chekaev, Фарид (Рroblems of engineering and professional education, 2022)
his article deals with the features of the decorative-applied solution of wooden buildings in Akmola. Folk craftsmen took into account the contrast artistic beauty of finely carved details against the background of a log wall. They created masterpieces of carved art, showing them with feeling and artistic image, using the texture of wood with ingenuity. Do not leave behind everything useful and valuable, because it will be used in the future. Deep knowledge and mastery of the heritage of folk architecture, accumulated over the centuries, shows invaluable help in today's modern architectural practice.